Analysis and characterization of iron pyrite nanocrystals and nanocrystalline thin films derived from bromide anion synthesis1. Issue 13 (7th April 2015) - Bhandari, Khagendra P.; Roland, Paul J.; Kinner, Tyler; Cao, Yifang; Choi, Hyekyoung; Jeong, Sohee; Ellingson, Randy J.
<x xml:space="preserve">Abstract</x> We use a solution-based bromide anion hot injection method to synthesize stable, phase pure and highly crystalline cubic iron pyrite (FeS2) nanocrystals, with size varying from ∼70 to ∼150 nm.